Effect of HPV on tumor expression levels of the most commonly used markers in HNSCC - Polanská, Hana; Heger, Zbyněk; Gumulec, Jaromír; Raudenská, Martina; Svobodova, Marketa; Balvan, Jan; Fojtů, Michaela; Binková, Hana; Horáková, Zuzana; Kostřica, Rom; Adam, Vojtěch; Kizek, René; et al. (Tumor biology, 2016)
Approximately 90 % of head and neck cancers are squamous cell carcinomas (HNSCC), and the overall 5-year survival rate is not higher than 50 %. There is much evidence that human papillomavirus (HPV) infection may influence the expression of commonly studied HNSCC markers. Our study was focused on the possible HPV-specificity of molecular markers that could be key players in important steps of cancerogenesis (MKI67, EGF, EGFR, BCL-2, BAX, FOS, JUN, TP53, MT1A, MT2A, VEGFA, FLT1, MMP2, MMP9, and POU5F). qRT-PCR analysis of these selected genes was performed on 74 biopsy samples of tumors from patients with histologically verified HNSCC (22 HPV-, 52 HPV+). Kaplan-Meier analysis was done to determine the relevance of these selected markers for HNSCC prognosis. In conclusion, our study confirms the impact of HPV infection on commonly studied HNSCC markers MT2A, MMP9, FLT1, VEGFA, and POU5F that were more highly expressed in HPV-negative HNSCC patients and also shows the relevance of studied markers in HPV-positive and HPV-negative HNSCC patients.
Keywords: studie případů a kontrol; stanovení celkové genové exprese; senioři nad 80 let; RNA, Messenger; Biomarkers, Tumor; Case-Control Studies; Humans; prognóza; stupeň nádoru; lidé; nádorové biomarkery; Real-Time Polymerase Chain Reaction; messenger RNA; Aged, 80 and over; Gene Expression Profiling; Carcinoma, Squamous Cell; Female; Papillomavirus Infections; polymerázová řetězová reakce s reverzní transkripcí; lidé středního věku; Prognosis; spinocelulární karcinom; infekce papilomavirem; Male; Survival Rate; staging nádorů; DNA virů; následné studie; DNA, Viral; Follow-Up Studies; Adult; nádory hlavy a krku; dospělí; Papillomaviridae; senioři; Neoplasm Grading; kvantitativní polymerázová řetězová reakce; Aged; Neoplasm Staging; míra přežití; Middle Aged; ženské pohlaví; mužské pohlaví; Head and Neck Neoplasms; Reverse Transcriptase Polymerase Chain Reaction